Helopeltis theivora (Heteroptera, Miridae) as a pest of betel vine (Piper betle) - SIVAKUMAR T; YESHWANTH H M (The Indian Journal of Agricultural Sciences, 2020)
Tea mosquito bug (TMB), Helopeltis theivora Waterhouse (Heteroptera, Miridae) has been recorded for the first time from Kerala, India, as a pest of betel vine (Piper betle L.). Nymphs and adults feed on the tender leaves making it unfit for consumption and sale. Angular water-soaked patches which later appear like shot holes were the symptoms of infestation. Neem oil soap emulsion (0.2%) was effective against the pest. The infested plot was not near tea or cashew plantations, which ruled out the possibility of opportunistic incidence of H. theivora on P. betle. Hence, it is evident that H. theivora has to be reckoned as a pest of betel vine. The current observation on betel vine is important as many of the betel vine growing states in the country are also known for large scale cultivation of tea. Host shift from tea to betel vine and vice versa in these areas may pose a challenge to the production of both the crops. An IPM module with safe organic pesticides has to be developed for contingencies in future.